"It's not all nice and fun": Narrating contested illness on YouTube and Instagram. (September 2022) - Groenevelt, Irene
This empirical study draws on insights from narrative theory to tease out how women with a contested illness narrate their experiences on social media. Based on 13 months of online observations between 2017 and 2019, I analyse how a sample of eight highly active Dutch female social media users share their illness on YouTube and Instagram. In addition, I interviewed five of them. Through their online performances, the women in this study illustrate their investment in self-care practices, whilst simultaneously laying bare the limits of these practices in ensuring permanent well-being. Central to transmitting their experiences is the performance of balanced positivity ; meaning that illness is dealt with in a predominantly 'positive' way, as well as through the occasional display of (moments of) hardship. I identify three main aspects of this performance of balanced positivity, namely: (1) appearances, (2) mindset, and (3) presence. The practice of balanced positivity is congruent with the concept of legitimacy narratives, because it allows women with a contested illness to show their efforts to cope with their condition as well as the myriad challenges that remain despite these efforts.